Rekonstruksi Pemikiran Hakim dalam Mewujudkan Supremasi Moral Justice - Hermawan, Vincent; Budiman, Sitti Nabila Yusri; Pasa, Alicia Putri; Gea, Lenggo Anastasia Briliant; Suwandy, Albert; Saly, Jeane Neltje (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this research is to find out how the judge profession thinks in realizing the supremacy of moral justice and what factors lead to violations of the code of ethics of the judge profession. Judges have a central role in ensuring justice and law run well. In carrying out their duties, judges must maintain the consistency of their decisions and accommodate changes in legal values ​​and a sense of justice that occur in people's lives. The judge must also understand that his position is transcendental and acts as a guardian of cosmic balance. Therefore, judges must strengthen their thinking in realizing the supremacy of moral justice. Reconstruction of judges' thoughts can help realize the supremacy of moral justice by maintaining the consistency of judges' decisions in upholding law and justice, accommodating changes in legal values ​​and a sense of justice that occur in people's lives, and increasing judges' understanding of the meaning of the supremacy of moral justice and its role in make it happen. In addition, judges must also develop a progressive law-based mindset to deal with social changes and values ​​that develop in society. In realizing the supremacy of moral justice, judges must understand that their position has a great responsibility in maintaining justice and law in society. Therefore, judges must strengthen their thinking in realizing the supremacy of moral justice by maintaining the consistency of decisions, accommodating changes in legal values ​​and a sense of justice, and increasing understanding of the meaning of the supremacy of moral justice and its role in realizing it. Thus, the reconstruction of judges' thinking can help realize the supremacy of moral justice and maintain justice and law in society.